Consecutive Utilization of Mechanochemical and Microwave Methods for the Synthesis of Boc‐2‐amino‐quinazolin‐4(3H)‐ones and DFT Study of Mechanism 6π‐Diazaelectrocyclization Process. Issue 13 (25th March 2022) - Antol, Ivana; Glasovac, Zoran; Murata, Yasujiro; Hashikawa, Yoshifumi; Margetić, Davor
Abstract: Two eco‐friendly synthetic methods were used consecutively in the preparation of quinazolin‐4( 3H )‐one heterocycles. The first reaction step, synthesis of a series of aryl guanidines was carried out by solvent‐free mechanochemical milling of aryl amines with 1H‐pyrazole‐ N, N ‐di‐( tert ‐butyloxycarbonyl)‐1‐carboxamidine. In the following synthetic step, aryl guanidines were converted into Boc‐2‐amino‐quinazolin‐4(3 H )‐ones by microwave heating. The experimental studies were supplemented by detailed quantum chemical studies (DFT) of the reaction mechanism of 6π‐diazaelectrocyclization process, and the predicted reactivities and regioselectivities are consistent with the experimental observations. Abstract : Sustainable organic synthesis Guanylation of aromatic amines and thermal electrocyclization could be carried out by consecutive employment of sustainable synthetic methods ‐ mechanosynthesis and microwave irradiation. Quantum‐chemical calculations DFT methods suggest the mechanistic details, with crucial involvement of solvation in the key processes ‐ elimination of Boc substituent and 1, 5 H‐shift. Relative reactivities and regioselectivities of series of aromatic guanidines was predicted correctly.